Has market discipline on banks improved after the Dodd–Frank Act? - Balasubramnian, Bhanu; Cyree, Ken B. (Journal of Banking & Finance, 2014)
We investigate whether or not market discipline on banking firms changed after the Dodd–Frank Wall Street Reform and Consumer Protection Act (DFA) of 2010. If market discipline is improved, we should see a lower discount for size on yield spreads, particularly for banks identified as too-big-to-fail (TBTF) or systemically important (SIFI). Using secondary market subordinated debt transactions we find that the size discount is reduced by 47% and TBTF discount is reduced by 94% after the DFA. The DFA has been effective in reducing, but not in eliminating the size and TBTF discounts on yield spreads. Market discipline of banks appears to have improved further after the rating criteria changes by Moody’s.